Femur strength predictions by nonlinear homogenized voxel finite element models reflect the microarchitecture of the femoral neck. (May 2020) - Iori, Gianluca; Peralta, Laura; Reisinger, Andreas; Heyer, Frans; Wyers, Caroline; van den Bergh, Joop; Pahr, Dieter; Raum, Kay
Highlights: Femur strength from mechanical tests and hvFE models was associated with the femoral neck bone density and microstructure. Nonlinear hvFE models captured the distinct contributions of cortical and trabecular bone for femur strength. The effect of varying direction of load was correctly reflected by hvFE models. Abstract: In the human femoral neck, the contribution of the cortical and trabecular architecture to mechanical strength is known to depend on the load direction. In this work, we investigate if QCT-derived homogenized voxel finite element (hvFE) simulations of varying hip loading conditions can be used to study the architecture of the femoral neck. The strength of 19 pairs of human femora was measured ex vivo using nonlinear hvFE models derived from high-resolution peripheral QCT scans (voxel size: 30.3 µm). Standing and side-backwards falling loads were modeled. Quasi-static mechanical tests were performed on 20 bones for comparison. Associations of femur strength with volumetric bone mineral density (vBMD) or microstructural parameters of the femoral neck obtained from high-resolution QCT were compared between mechanical tests and simulations and between standing and falling loads. Proximal femur strength predictions by hvFE models were positively associated with the vBMD of the femoral neck (R² > 0.61, p  < 0.001), as well as with its cortical thickness (R² > 0.27, p  < 0.001), trabecular bone volume fraction (R² = 0.42, p  < 0.001) and with the first two principal components of the femoral neck architecture (R² > 0.38, p  < 0.001). Associations between femur strength and femoral neck microarchitecture were stronger for one-legged standing than for side-backwards falling. For both loading directions, associations between structural parameters and femur strength from hvFE models were in good agreement with those from mechanical tests. This suggests that hvFE models can reflect the load-direction-specific contribution of the femoral neck microarchitecture to femur strength.